A comparison of anterior reconstruction of spinal defect using nano-hydroxyapatite/polyamide 66 cage and autologous iliac bone for thoracolumbar tuberculosis: a stepwise propensity score matching analysis - Li, Qiujiang; Xiu, Peng; Yang, Xi; Wang, Lei; Liu, Limin; Song, Yueming (Frontiers in Bioengineering and Biotechnology, 2024)
Previous studies have confirmed the advantages and disadvantages of autogenous iliac bone and nano-hydroxyapatite/polyamide 66 (n-HA/PA66) cage. However, there is no conclusive comparison between the efficacy of the two implant materials in spinal tuberculosis bone graft fusion. The aim of this study was to analyze the mid-to long-term clinical and radiologic outcomes between n-HA/PA66 cage and autogenous iliac bone for anterior reconstruction application of spinal defect for thoracolumbar tuberculosis. Methods: We retrospectively reviewed all patients who underwent anterior debridement and strut graft with n-HA/PA66 cage or iliac bone combined with anterior instrumentations between June 2009 and June 2014. One-to-one nearest-neighbor propensity score matching (PSM) was used to match patients who underwent n-HA/PA66 cage to those who underwent iliac bone. Clinical outcomes were assessed using the Japanese Orthopaedic Association (JOA) and visual analogue score (VAS). Radiographic evaluations included cage subsidence and segmental angle. Results: At the end of the PSM analysis, 16 patients from n-HA/PA66 cage group were matched to 16 patients in Iliac bone group. The C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) values in the n-HA/PA66 group decreased significantly from 33.19±10.89 and 46.63±15.65 preoperatively, to 6.56±2.48 and 9.31±3.34 at the final follow-up, respectively (P<0.001). There were no significant differences in the CRP and ESR values between the two groups at the final follow-up. The VAS and JOA scores in the iliac bone and n-HA/PA66 group were significantly improved at the 3-month follow-up postoperatively (both P<0.001). Then, improvements of VAS and JOA scores continue long at final follow-up. However, there were no significant differences in the VAS and JOA scores at any time point between the two groups (P>0.05). Although the segmental angle (SA) significantly increased after surgery in both groups, there was no significant difference at any time point after surgery (P>0.05). There were no significant differences in the cage subsidence and fusion time between the two groups. Conclusion: Overall, our data suggest that the n-HA/PA66 cage outcomes are comparable to those in the autogenous iliac bone, with a similar high fusion rate as autogenous iliac bone.